Increase in American Joint Committee on Cancer Stage at Diagnosis for Patients with Skin Cancers after the COVID-19 Lockdown - Charlée Nardin; Lise Senot; Paul Pernot; Eve Puzenat; François Aubin; Lucas Morin (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)